Reinstatement of the East African Asplenium aequilaterale (Aspleniaceae), and resolution of its synonymy - Crouch, Neil R.; Hemp, Andreas; Smith, Gideon F. (Phytotaxa, 2024)
Following the valid publication in 1894 of the name Asplenium [‘Asplenum’] anisophyllum Kunze (1836: 511) var. aequilaterale Hieronymus in Engler (1894: 45) in the fern family Aspleniaceae for an East African taxon, and the further valid publication of this varietal name in Engler’s Die Pflanzenwelt Ost-Afrikas und der Nachbargebiete, Deutsch-Ost-Afrika the following year (Hieronymus 1895: 82), as Asplenium [again as ‘Asplenum’] anisophyllum Kunze (1836: 511) var. aequilaterale [‘aequilateralis’] Hieronymus in Engler (1895: 82), it seemingly remained unnoticed by pteridologists for nearly a century. Viane & Reichstein (1992) have pointed out that the name was not even listed in the Index Filicum of Christensen (1906) and Supplements, on which account it may have been overlooked in later relevant literature that includes Peter (1929), Faden (1973, 1974), and Jacobsen & Jacobsen (1989). Along with a specimen accessioned to Herb. B (Holst 2491), Viane & Reichstein (1992) relied on material collected by R.R. Schippers, held at Wageningen (Herb. WAG), to assess the status and position of Hieronymus’s variety. They deemed it recognisable at species rank and, accordingly, Viane published the name A. aequilaterale (Hieronymus in Engler 1895: 82) Viane in Viane & Reichstein (1992: 157), with Holst 2491 at Herb. B cited as the “holotype”. They recognised that the affinity of their species was not with A. anisophyllum in its present circumscription, but rather with the tropical African A. macrophlebium Baker in Hooker & Baker (1874: 485). The terrestrial A. aequilaterale was considered to grow in mid-montane forests between elevations of 1350 and 1950 m, within the South Pare and West Usambara mountains (Viane 1992). Schippers (1993) shortly thereafter extended the range of A. aequilaterale to include the North Pare mountains of Tanzania, and the Teita Hills of Kenya. He described it as a relatively common steep forest floor inhabitant, particularly in the South Pare and West Usambara mountains.